Impact Analysis of Pt. X Scholarship Program to Improve the Quality of Students at State Universities - Widyastomo, Rinadi Nugroho; Nilasari, B Medina (International Journal Labs, 2023)
The purpose of this study is to analyze the impact of the scholarship program provided by PT X through the Corporate Social Responsibility program to students at 2 State Universities, in addition to its impact on student achievement, but also examines its relationship with Sustainable Development Goals No. 4 Quality Education. The subjects of this study were students who received PT. X scholarships at two state universities. This research is a qualitative research. The types of data used are primary and secondary data. Primary data was obtained from in-depth interviews and secondary data was obtained from Activity Reports related to the implementation of this program. Data collection techniques were carried out by observation, interview and documentation. The results of this study indicate that the PT. X Scholarship Program has a positive impact on its recipients and has an impact on the implementation of SDGs No. 4, but no impact and benefits have been found for the recipients after they graduate and are no longer part of the PT. X scholarship recipients.